Spatial inter-comparison of Top-down emission inventories in European urban areas. (January 2018) - Trombetti, Marco; Thunis, Philippe; Bessagnet, Bertrand; Clappier, Alain; Couvidat, Florian; Guevara, Marc; Kuenen, Jeroen; López-Aparicio, Susana
Abstract: This paper presents an inter-comparison of the main Top-down emission inventories currently used for air quality modelling studies at the European level. The comparison is developed for eleven European cities and compares the distribution of emissions of NOx, SO2, VOC and PPM2.5 from the road transport, residential combustion and industry sectors. The analysis shows that substantial differences in terms of total emissions, sectorial emission shares and spatial distribution exist between the datasets. The possible reasons in terms of downscaling approaches and choice of spatial proxies are analysed and recommendations are provided for each inventory in order to work towards the harmonisation of spatial downscaling and proxy calibration, in particular for policy purposes. The proposed methodology may be useful for the development of consistent and harmonised European-wide inventories with the aim of reducing the uncertainties in air quality modelling activities. Highlights: Assessment of inconsistencies between Top-down emission inventories at the European scale. First step towards harmonisation of spatial proxies for emission distribution. Tools for comparison of downscaled emissions at different levels are presented. Urban Emissions of NOx, PPM2.5, SOx and VOC from SNAP02, 34 and 07 are compared.